High Blood Pressure and Its Associated Factors Among Aksum University Students, Northern Ethiopia, 2019: A Cross-Sectional Study - Gebreamlak Gebremedhn Gebremeskel; Teklehaimanot Gereziher Haile; Gebremeskel Tukue Gebrewahd; Degena Bahrey Tadesse (Frontiers Media S.A., 2024)
Objectives:This study aimed to assess the burden of high blood pressure and its associated factors among students at Aksum University.Methods:A total of 240 participants were included; participants were selected through simple random sampling from May 2019 to July 2019. Logistic regression analysis was performed, with statistical significance set at a p-value <0.05 and a 95% confidence level.Results:This study found that 17.9% of the participants had high blood pressure, with higher rates observed in males (62.79%) than in females (37.21%). Several factors were identified as associated with high blood pressure, including a family history of high blood pressure [AOR 1.72, 95% CI (1. 75-4.04)], regular physical exercise [AOR 0.64, 95% CI (0.30-0.94)], alcohol consumption [AOR 2.16, 95% CI (1.07-4.62)], tobacco smoking [AOR 5.46, 95% CI (1.98-15.07)], and central obesity [AOR 2.72, 95% CI (1.12-6.58)].Conclusion:This study reveals that one out of six students had high blood pressure. Factors such as a family history of high blood pressure, physical inactivity, tobacco smoking, and central obesity were associated with this condition.